Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1038/s41598-022-21471-2
|View full text |Cite
|
Sign up to set email alerts
|

Threat learning impairs subsequent associative inference

Abstract: Despite it being widely acknowledged that the most important function of memory is to facilitate the prediction of significant events in a complex world, no studies to date have investigated how our ability to infer associations across distinct but overlapping experiences is affected by the inclusion of threat memories. To address this question, participants (n = 35) encoded neutral predictive associations (A → B). The following day these memories were reactivated by pairing B with a new aversive or neutral ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
3
2
0
Order By: Relevance
“… 56 ). The relatively low vividness score for emotional memories is consistent with a previous study in which a similar paradigm was used and may reflect decreased unitization of separate items in memory 57 .
Figure 3 Vividness ratings during the encoding task in the Same Context Exposure (blue bars), Similar Context Exposure (red bars), and No Exposure group (grey bars).
…”
Section: Resultssupporting
confidence: 88%
“… 56 ). The relatively low vividness score for emotional memories is consistent with a previous study in which a similar paradigm was used and may reflect decreased unitization of separate items in memory 57 .
Figure 3 Vividness ratings during the encoding task in the Same Context Exposure (blue bars), Similar Context Exposure (red bars), and No Exposure group (grey bars).
…”
Section: Resultssupporting
confidence: 88%
“…Then, after each CS -> US association had been presented in the first learning block, pupil dilation to CS+ was higher than to CS-in block 2 (difference = 0.046 mm, CI95 = [0.011, 0.081], p = 0.011) and block 3 (difference = 0.088 mm, CI95 = [0.053, 0.124], p < 0.001). This observation replicates our earlier work using the episodic conditioning paradigm (de Vries, Duken, et al, 2022;de Vries, Grasman, et al, 2022). Crucially, pupil dilation to CS+ remained higher than to CS-the following day (difference = 0.057 mm, CI95 = [0.030, 0.083], p < 0.001), indicating that direct conditioned responses were retained at the time sensory preconditioning was tested.…”
Section: Conditioned Responses Are Acquired On Day Two and Retained O...supporting
confidence: 88%
“…Participants of which over 50% trials were excluded in either condition were excluded from the analysis altogether (de Vries, Duken, et al, 2022;de Vries, Grasman, et al, 2022).…”
Section: Data Acquisition and Processingmentioning
confidence: 99%
“…Vividness of the imagined scenes during encoding was lower for negative 20 than neutral memories (Emotion, F1,150 = 7.08, p = .009, Fig. 3), in line with earlier research (de Vries et al, 2022). Crucially, there were no significant differences in vividness between the Same Context Exposure, Similar Context Exposure, and No Exposure groups (Context (Re)exposure, F2,150 = 0.14, p = .869).…”
Section: Manipulation Checkssupporting
confidence: 87%
“…We have recently shown that this can be accomplished by using words for central events (Cox, Dobbelaar, et al, 2021). Presenting images of objects could also be a more effective way to induce unique episodic events (de Vries et al, 2022). Apart from difficulties in the formation of complete episodic memories during learning, the relatively little time to encode new or lost contextual information during context (re)exposure could also have been a limiting factor on integration.…”
Section: Discussionmentioning
confidence: 99%